G586(P) Case report of hyper igm syndrome in down syndrome child. (25th October 2020) - Quek, MC; Migowa, A; Gitakah, RW
Abstract : Introduction: Down syndrome is the most common genetic disease that often presents with a high frequency of infections especially upper airway infections in their early years, characterized by increased severity and prolonged course of disease. Individuals with Down syndrome are known to have abnormal function of the B-cell function, which might present with high IgG and low IgM serum level. Case Description: A one-year-old known Down syndrome child presented with persistent nasal congestion, fever, noisy breathing, and daily cough for 8 months. He had several outpatient consults and treatment with antibiotics but with poor relief of symptoms. Due to persistent symptoms, he was referred to the ENT surgeon. His paranasal radiographs revealed sinusitis. He was then referred to a pediatric infectious specialist for further management. Examination revealed a sick-looking, syndromic child who was having marked nasal congestion, global hypotonia and generalized erythematous rash. He was well-nourished. Serum immunoglobulin test show marked elevated Ig M with low Ig G and Ig A levels. Rheumatologist agreed with the possible diagnosis of primary immunodeficiency syndrome (PIDS). Pulmonologist confirmed no underlying congenital lung pathology from the chest CT scan. The echocardiogram was unremarkable. He received intravenous immunoglobulin (IVIG) as part of the therapy and his symptoms improved markedly. An impression of Hyper Ig M syndrome was made. He received two other courses of IVIG after discharge. Currently, the mother reports good improvement of symptoms. Discussion: Hyper IgM syndrome is a primary immunodeficiency syndrome characterized by defective CD 40 signaling, which leads to a defect in Ig class switching recombination. The association of Down syndrome with PIDS is not clearly demonstrated. In our case, elevated Ig M was an incidental finding. Warning signs present in children with Down syndrome warrants a detailed immunology investigation to exclude primary immunodeficiency. Diagnosing PIDS imposed a great challenge to doctors especially due to the co-existing condition. A delay in diagnosis is common and associated with increased morbidity and parental distress. Conclusion: There is a need to create awareness amongst the healthcare workers concerning PIDS especially in children with co-existing diseases. We need to assure the proper diagnosis and proper care management are provided to the affected children.